Nasal diphtheria (chronic carriage) caused by nontoxigenic Corynebacterium diphtheriae. Issue 9 (September 2018) - Okamoto, Koh; Hatakeyama, Shuji; Sugita, Chise; Ogura, Kenichi; Ueda, Reiko; Kouda, Hiroko; Nakata, Junko
Abstract: Toxigenic strains of Corynebacterium diphtheriae cause the majority of respiratory diphtheria cases. However, nontoxigenic strains of C. diphtheriae can also cause diseases, and have become increasingly common. Infection that is limited to the anterior nares (nasal diphtheria) is a well-described but rare condition, even for toxigenic C. diphtheriae . We report a case involving chronic carriage of nasal diphtheria caused by nontoxigenic C. diphtheriae, as well as a review of other reported nontoxigenic C. diphtheriae cases in Japan. Mild or asymptomatic nasal diphtheria involving nontoxigenic strains, which can be the source of transmission, may be underrecognized. Our case highlights the importance of awareness regarding nontoxigenic diphtheria among clinicians, especially in the era of improved diphtheria vaccination coverage.